Augmented participatory action research in the digital age: Guidelines for implementation in community-based peatland restoration and sustainable business development - Purnomo, H.; Puspitaloka, D.; Juniyanti, L.; Kusumadewi, S.D.; Andrianto, A.; Okarda, B.; Basuki, I.; Muhammad, A.; Junandi, B.; Sutikno, S.; Kurniawan, S.; Qomar, N.; et al. (Center for International Forestry Research, 2023)
Participatory Action Research (PAR) is a tool for fostering a new paradigm in natural resources management. Combined with an Adaptive Collaborative Management (ACM) approach, in community-based fire prevention and peatland restoration, PAR facilitates transformative change through a simultaneous process of research and taking action, linked together by critical refl ection. Covid-19 led to the transformation of traditional PAR to become a new incarnation aided by internet technology, remote connections and new ways of implementing collaboration. This new incarnation, which we refer to as augmented PAR, consists of a spiral of refl ection and co-elevation, co-creation and planning, connected actions, and monitoring and co-learning phases. External reinforcement can strengthen actions and improve augmented PAR processes. This book, which constitutes part of the Toolbox on Community-based Fire Prevention and Peatland Restoration, presents case studies from Kayu Ara Permai and Penyengat villages in Riau Province, where PAR on community-based fi re prevention and peatland restoration is taking place from 2021 to 2023. We hope it can serve as a reference for actors involved in sustainable peatland management and restoration in reconciling ecological, social and economic objectives.